2021
DOI: 10.1111/scs.12983
|View full text |Cite
|
Sign up to set email alerts
|

Professional governance in Finnish nursing – measured by the Index of Professional Nursing Governance

Abstract: To translate and validate the Index of Professional Nursing Governance (IPNG) 2.0 and assess the state of professional nursing governance in Finland. Background: Raising and maintaining quality of care while retaining staff are common problems in healthcare globally. Professional governance is a modern way to tackle them, but a reliable instrument is needed to measure the state of nursing governance in Finland, and elsewhere. Methods: The IPNG that was translated into Finnish by forward-backward translation, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Most public health nursing staffs specialize in a number of areas, such as the prevention and care of infectious diseases, maternal and child health care services, school health services, etc. Therefore, they can provide a wide range of public health nursing services to community groups and meet community residents' daily health nursing needs [3].…”
Section: Overview Of Public Health Nursingmentioning
confidence: 99%
“…Most public health nursing staffs specialize in a number of areas, such as the prevention and care of infectious diseases, maternal and child health care services, school health services, etc. Therefore, they can provide a wide range of public health nursing services to community groups and meet community residents' daily health nursing needs [3].…”
Section: Overview Of Public Health Nursingmentioning
confidence: 99%
“…Interest in the Magnet model has influenced nursing management in Finnish health care, and the same ideology is included in nursing strategies in Finland [ 1 ]. Kanninen et al [ 10 ] found that nurse managers felt that decision-making power in daily nursing matters was extended to the nurses, and they have good control over their practice, as well as the ability to set goals and resolve issues. However, in the same study, nurses reported that they hardly have any impact in decision making and that their organization’s governance style was traditional.…”
Section: Introductionmentioning
confidence: 99%
“…In a healthy work environment, there is both good communication and constructive collaboration, with all professionals involved enabled to contribute to effective decision making. This can be regarded as professional governance (Kanninen et al, 2021; Porter‐O'Grady & Pappas, 2022), which can come close to professional autonomy. During times of crisis, leaders may have to make decisions without the time to listen to their staff, and nurses have to respond directly to doctors' instructions during the course of frontline patient care.…”
mentioning
confidence: 99%
“…While it is possible to participate in traditional shared governance, focusing on responsibility, where nurses and managers share locally based decisions, Grubaugh and Bernard (2022) suggest there is a need to move on and progress to true professional governance. This encompasses an expectation of real expertise, autonomy and participation in intraprofessional decision making (Kanninen et al, 2021). Building relationships, creating partnerships, and working with numerous teams is required in complex health care.…”
mentioning
confidence: 99%
See 1 more Smart Citation